2017
DOI: 10.1097/md.0000000000006903
|View full text |Cite
|
Sign up to set email alerts
|

Timing of preoperative antibiotic prophylaxis in 54,552 patients and the risk of surgical site infection

Abstract: Supplemental Digital Content is available in the text

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
114
1
3

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 144 publications
(122 citation statements)
references
References 39 publications
(137 reference statements)
4
114
1
3
Order By: Relevance
“…(24,25) The use of the checklist can support adherence, and this study demonstrated that the impact factor for SSI reduction was the adherence to the antibiotic administration schedule evidenced by checking antibiotic prophylaxis in the second period of the checklist administration, before the skin incision. During the period prior to the implementation of the checklist, there was no institutional control of proper surgical prophylaxis.…”
Section: Discussionmentioning
confidence: 99%
“…(24,25) The use of the checklist can support adherence, and this study demonstrated that the impact factor for SSI reduction was the adherence to the antibiotic administration schedule evidenced by checking antibiotic prophylaxis in the second period of the checklist administration, before the skin incision. During the period prior to the implementation of the checklist, there was no institutional control of proper surgical prophylaxis.…”
Section: Discussionmentioning
confidence: 99%
“…As mentioned, guidelines have indicated that prophylactic antibiotics should be given at least one hour before surgery, although others have indicated longer, and stopped 24 h after the initial incision [4,22,23]. In case of contaminated and dirty wounds, presumptive treatment should be undertaken [21].…”
Section: Case Definitionmentioning
confidence: 99%
“…Surgical site infections (SSIs) increase morbidity, mortality and costs, and can be particularly problematic in low and middle income countries (LMICs) [1][2][3][4][5]. They are a common cause of hospital acquired infections, and can be common after certain surgical procedures [6,7].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although surgeons follow a certain protocol for antibiotic therapy after open heart surgeries, due to the potentially hazardous post cardiac surgery infections, the duration and type of prophylactic antibiotic remains a controversial challenge (3,4). Surgical site infection has always been an expensive and uncomfortable problem, and in particular, cardiovascular surgery may have devastating consequences and can occur as an infectious problem in 3-10% of cases (5).…”
Section: Introductionmentioning
confidence: 99%